ABILITY TO WRITE SHORT MESSAGE ACCORDING TO THE CONTENTS THROUGH THE MEDIA CARDS TO JUNIOR HIGH SCHOOL SEVENTH GRADERS ALWASHLIYAH 24 - Sihombing, Nisma; Muliatik, Sri; Zahara, Siti Fatimah (Program Studi Pendidikan Bahasa Indonesia FKIP-UNIVA Medan, 2022)
The purpose of this study was to determine the ability to write short messages according to the content through card media in class VII Al-Washliyah 24 Medan students. This study used a qualitative descriptive method, which the authors describe the results of research on writing short messages carried out by researchers and students of class VII Al-Washliyah 24 Medan, amounting to 50 people. data retrieval in this study was carried out with observation, documentation and interview techniques. In the learning activities the teacher uses Indonesian language books and card media and short text messages. The results of this study indicate that the activity of writing short messages according to the contents through the media card has met the learning criteria. Attitude assessment is carried out through observation and documentation. Assessment of short message writing skills is carried out through interview tests or tests in accordance with the research instrument. The conclusions obtained are that the short message writing skills in class VII students of Al_Washliyah 24 Medan Junior High School have met the learning criteria.